The immunomodulating role of probiotics in the prevention and treatment of oral diseases - Marta Kaźmierczyk-Winciorek; Małgorzata Nędzi-Góra; Sylwia Małgorzata Słotwińska (Central European Journal of Immunology, 2021)
Probiotics are defined as non-pathogenic live microorganisms which, when administered in appropriate amounts, are beneficial to the health of the host. Currently, the group of probiotic microorganisms includes bacteria that produce lactic acid of the genera Lactobacillus and Bifidobacterium, belonging to the so-called LAB (lactic acid bacteria) groups, and the yeast Saccharomyces boulardii. Probiotics have a protective role in Candida spp. oral infection and especially colonization. Lactobacillus limits the progression of chronic periodontitis by inhibiting the secretory activity of Th17 lymphocytes, which in the pathogenesis of this disease are responsible for an excessive cytokine response causing adverse changes in periodontal tissues. A meta-analysis of the results of studies on the clinical evaluation of the effectiveness of probiotics in the treatment of gingivitis showed that the use of probiotics improved the condition of the gums in the course of the therapeutic process. Regular use of probiotics during orthodontic treatment significantly reduces the number of bacteria from the Streptococcus mutans group in the patient’s saliva and significantly inhibits the expression of inflammatory mediators and an excessive immune response. The main mechanisms of the action of probiotics, such as elimination and inhibition of the growth of pathogenic microorganisms through competition for receptor sites and the secretion of metabolites with antibacterial activity, as well as the stimulation of specific and non-specific immune responses by activating T lymphocytes, and stimulating the production of cytokines, make it possible to also effectively use pro-health bacteria in oral diseases.